Determination of loading modes for endurance tests of reinforced concrete sleepers on the basis of experimental measurement of their stress state under the conditions of the Test Loop at Shcherbinka - O. A. Suslov; N. V. Ressina; A. V. Portnov; A. A. Novikov; V. A. Mariychuk (Вестник Научно-исследовательского института железнодорожного транспорта, 2021)
The article considers the issue of changing the stressstrain state of reinforced concrete sleepers depending on the value of the axle loads and the requirements for the modes of its bench endurance tests. This issue is very relevant, since at present, in certain sections of the network (directions of the Eastern operational area), due to the high traffic density, the impact on the track increases and the axle load increases. Such a change entails the need to revise the requirements for the methods for determining and confirming the resource of all track elements, including the loading modes of reinforced concrete sleepers during its bench tests. To determine the influence of the axle load, measurements were made of the actual stress-strain state of reinforced concrete sleepers laid on the tangent section of the Test Loop of the JSC “VNIIZHT”. The loading was realized by a running train of 72 cars and a specially formed experimental coupler of a locomotive and three cars with an axle load of 23.5, 25 and 27 tf, respectively. Measurements made it possible to obtain the dependence of the change in stresses and deformations on the change in the axle load, as well as to reveal the rheological features of the interaction of reinforced concrete sleepers and the ballast layer. Obtained measurement results were used as basic stresses and strains for calculating loading modes in bench endurance tests. Purpose of the calculation is to achieve the maximum identity of the stress state when the sleepers are loaded on the bench with its stress state during real operation. In addition, experimental bench loading of a reinforced concrete sleeper was carried out, during which the modes obtained by the calculation were implemented and its stress-strain state was measured. Results of comparing the stress state of a reinforced concrete sleeper obtained during full-scale measurements on the way and during loading on the stand showed their identity, which confirmed the adequacy of the calculated loading modes. The final result of the work was the loading modes for bench tests of reinforced concrete sleepers, taking into account the influence of the axle load value.